Women in sports : 50 fearless athletes who played to win - Ignotofsky, Rachel, 1989- (Ten Speed Press, 2017)
"Illustrated profiles of fifty pioneering female athletes, from the author of the New York Times bestseller Women in Science. A charmingly illustrated and inspiring book, Women in Sports highlights the achievements and stories of fifty notable women athletes--from well-known figures like tennis player Billie Jean King and gymnast Simone Biles, to lesser-known athletes like skateboarding pioneer Patti McGee and Toni Stone, the first woman to play baseball in a men's professional league. Covering more thanforty sports, this fascinating collection also contains infographics about notable women's teams throughout history,pay and media statistics for female athletes, and muscle anatomy. Women in Sports celebrates the success of the tough, bold, and fearlesswomen who paved the way for the next generation of athletes"--